Trends and Patterns of Foreign Direct Investment Inflows in Karnataka (Global Journal of Human-Social Science, 2023)
Since the New Economic Policy in India, Foreign Direct Investment (FDI) has received more attention at both national and state levels. According to the World Investment Report (2021) published by UNCTAD, India is one of the top investment destinations and ranks 7th place in receiving FDI inflows. While attracting inflows from all the regions, Karnataka garners a larger share among the total FDI inflows in India. This paper examines the trends and patterns of Foreign Direct Investment (FDI) inflows in the state of Karnataka in the past decade (2012-13 to 2021-22) with emphasis on investment promotion policies, comparative performance among the top five states of India, cumulative inflows from abroad and challenges for the state to further strengthen the inflows. It is hypnotized that FDI has a positive impact on Per Capita Net State Domestic Product (NSDP) and infrastructure development in the state. The multi-regression analysis is used as a statistical tool.
Keywords: foreign direct investment; non-debt creation; multi-dimensional aspects; policy promotions; growth implications